L’évolution des charpentes d’églises du Val d’Oise, du XIe au XXe siècle - Frédéric Epaud; Vincent Bernard (Revue Archéologique du Centre de la France)
From 2003 to 2006 a study of church roofs in Val d'Oise was performed within the framework of SDAVO to to outline the development of structures and techniques of carpentry from 11th to 20th century. 150 roofs were observed, from all periods, with particular emphasis on those that most typified each type and period. If several unknown Romanesque roofs were discovered, the rest belong to a relatively known repertoire. There are a large number of Gothic roofs of the first third of 13th century (12% of the corpus) and for the most part unpublished. Several of them show a perfect mastery of 'fermes et pannes' (bent and purlins) towards 1230 and of its widespread nature in the religious architecture in Ile-de-France in this period, to the detriment of 'chevrons-formant-fermes' (common rafters forming a bent) which survive until 16th century only for their vaulting. The post-medieval roofs betray a drop in the quality of wood used, which accompanied the loss of carpentry skills at the beginning of 20th century.